2015
DOI: 10.1016/j.rmed.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of pirfenidone for idiopathic pulmonary fibrosis: An Italian real life study

Abstract: In this national experience, pirfenidone reduced the rate of annual FVC decline (p = 0.065). Since pirfenidone provided significant treatment benefit for patients with moderate-severe disease, our results suggest that the drug may also be effective in patients with more advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
53
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 19 publications
18
53
2
3
Order By: Relevance
“…With regard to attenuation of decline in FVC, the results of the analysis according to the GAP index staging system confirmed that, compared with patients with less advanced disease (GAP stage I), those with more advanced disease (GAP stages II and III) could benefit the most from the administration of pirfenidone ( p-value for homogeneity of difference between strata of 0.041). Ultimately, in this trial, as already reported by LOEH et al [23], 16 (12.5%) out of 128 patients improved their FVC by >10% during therapy with pirfenidone [24]. Only 22 (17.1%) patients out of 128 were treated with lower than the standard dose of the drug (2403 mg·day −1 ); however, such dose reduction did not influence the outcomes.…”
supporting
confidence: 70%
See 4 more Smart Citations
“…With regard to attenuation of decline in FVC, the results of the analysis according to the GAP index staging system confirmed that, compared with patients with less advanced disease (GAP stage I), those with more advanced disease (GAP stages II and III) could benefit the most from the administration of pirfenidone ( p-value for homogeneity of difference between strata of 0.041). Ultimately, in this trial, as already reported by LOEH et al [23], 16 (12.5%) out of 128 patients improved their FVC by >10% during therapy with pirfenidone [24]. Only 22 (17.1%) patients out of 128 were treated with lower than the standard dose of the drug (2403 mg·day −1 ); however, such dose reduction did not influence the outcomes.…”
supporting
confidence: 70%
“…Mean±SD FVC was 72±20% predicted, VC was 72±20% predicted and DLCO was 35±15% predicted. Multidisciplinary discussion was the diagnostic basis in 108 (21.8%) patients and, in order to obtain adequate lung specimens, histology was performed in 171 (34.1%) patients (as opposed to 25% of the Italian study [24]). The authors compared the data from their national registry to those of recent randomised clinical trials: patients in INSIGHTS-IPF were the same age as patients in ASCEND [8] and PANTHER [32], but were older than those in the two INPULSIS studies [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations